2020
DOI: 10.1016/j.cels.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

SERGIO: A Single-Cell Expression Simulator Guided by Gene Regulatory Networks

Abstract: Highlights d SERGIO simulates stochastic gene expression in steadystate or differentiating cells d Simulations of RNA splicing enable RNA velocity estimation from generated data d Simulations show technical noise to greatly impact accuracy of network inference d Simulations recapitulate key regulators of T cell differentiation program

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(153 citation statements)
references
References 94 publications
(143 reference statements)
4
149
0
Order By: Relevance
“…BEELINE [126] optimized SINGE's hyperparameters and constructed much smaller ensembles than we do in this study. SER-GIO's ensembling [130] was much closer to ours except for differences in the treatment of the λ hyperparameter. In the SERGIO evaluation, SINGE was the best GRN method when inferring networks from simulated datasets with added technical noise.…”
Section: Benchmarking and Evaluationsupporting
confidence: 51%
See 1 more Smart Citation
“…BEELINE [126] optimized SINGE's hyperparameters and constructed much smaller ensembles than we do in this study. SER-GIO's ensembling [130] was much closer to ours except for differences in the treatment of the λ hyperparameter. In the SERGIO evaluation, SINGE was the best GRN method when inferring networks from simulated datasets with added technical noise.…”
Section: Benchmarking and Evaluationsupporting
confidence: 51%
“…One evaluation of network inference algorithms on simulated single-cell datasets reported that their performances were only slightly better than a random edge ordering [129]. New single-cell gene expression simulators designed specifically for simulating GRNs [126,130] can help inform which GRN inference methods are best for different types of biological trajectories. Both of these studies evaluated SINGE performance with their GRN simulators but with different ensembling strategies.…”
Section: Benchmarking and Evaluationmentioning
confidence: 99%
“…We also simulated scRNA-seq data using a parametric method with a predefined scGRN model (see Experimental Procedures for details). 28 With the simulated data, which contain 100 genes and up to 3,000 cells, we compared constructed scGRNs against the ground truth (i.e., the simulated scGRN) to estimate the accuracy of reconstruction. We tested the accuracy of scTenifoldNet/PC regression against methods based on Spearman’s correlation coefficient (SCC) and mutual information (MI) 1 and on GENIE3.…”
Section: Resultsmentioning
confidence: 99%
“…We generated our own synthetic datasets using SERGIO, a single-cell expression simulator guided by GRNs. 28 SERGIO allows for the simulation of scRNA-seq data while considering the linear and non-linear influences of regulatory interactions between genes. SERGIO takes a user-provided GRN to define the interactions and generates expression profiles of genes in steady state using systems of stochastic differential equations derived from the chemical Langevin equation.…”
Section: Methodsmentioning
confidence: 99%
“…We first used the simulated data to validate the relevance of our method. We generated a synthetic scRNA-seq data set using the simulator SERGIO-a single-cell expression simulator guided by GRNs [10]. To simulate the data, we supplied SERGIO with a predefined GRN with five co-expression modules of different sizes (containing 5, 10, 25, 40, and 20 genes, respectively).…”
Section: Substep 13 Denoising Adjacency Matrices To Obtain the Finamentioning
confidence: 99%